(untitled) - Curren, Anna M. (San Diego, 1995)
Math for Meds reflects on every page an unmatched clinical reality. Actual drug labels, hypodermic syringe calibrations and realistic medication orders are combined to make all examples and tests uniquely "real." Transfer of calculation skills to clinical practice becomes totally nonthreatening as a result of this trend-setting instructional approach
Keywords: Pharmaceutical arithmetic,Số học dược phẩm; Programmed instruction,Hướng dẫn lập trình